1964
DOI: 10.1172/jci104963
|View full text |Cite
|
Sign up to set email alerts
|

Vasoactive Mediators as the “Trigger Mechanism” of Endotoxin Shock*

Abstract: The mechanisms by which endotoxin induces a profound shock state have not been clearly established. Several neurohumoral agents have been implicated as mediators of endotoxin shock. These include histamine (1-4), catecholamines (5-7), and serotonin (7-9).Inferences of the role played by any of these mediators have been derived from four types of evidence: a) the hemodynamic alterations observed in endotoxemia are simulated by vascular effects of the naturally occurring substance (4, 5), b) plasma concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
0

Year Published

1966
1966
1978
1978

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 47 publications
2
6
0
Order By: Relevance
“…These findings confirm and extend the observations of others (22,24,25). The factors that sustain the hemodynamic and metabolic alterations in endotoxin shock remain largely undefined.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…These findings confirm and extend the observations of others (22,24,25). The factors that sustain the hemodynamic and metabolic alterations in endotoxin shock remain largely undefined.…”
Section: Resultssupporting
confidence: 90%
“…Neither the magnitude nor the duration of the epinephrine concentrations approached that necessary for epinephrine intoxication (17,18). Whereas some investigators (19,20) have reported that endotoxin accentuates the vascular action of small amounts of epinephrine, this additive effect has not been observed in endotoxemic dogs (21)(22)(23).…”
Section: Resultsmentioning
confidence: 99%
“…There appears to be little support for the hypothesis [26] that vaso dilator agents are necessary in the treatment of acute canine endotoxine mia and our observations are consistent with the assumption that the beneficial effect of isoproterenol is related to actions other than systemic vasodilatation [25], Similar to the experiments reported by Spink et al [24], the level of circulating catecholamines was not excessively high in our animals and was considerably lower than in bled dogs [10]. This, and the observation that reserpine premedication fails to improve toler ance to endotoxinemia [15] support the assumption that the toxic effect of endotoxin is not caused primarily by the action of increased catecho lamine release [24],…”
Section: Discussionsupporting
confidence: 92%
“…Of particular concern has been a definition of the exact mechanims by which this form of shock is set into motion (3,9,11). Early cardiovascular changes have been noted which appear to follow the release of neurohumeral agents into the blood stream (1, 2, 5 , 9 ) .…”
mentioning
confidence: 99%
“…Early cardiovascular changes have been noted which appear to follow the release of neurohumeral agents into the blood stream (1, 2, 5 , 9 ) . Vasoactive materials such as histamine, serotonin, bradykinin, and the catecholamines have all been implicated as being involved in the earlier phases of endotoxin shock ( 2 , 3,5,9). Reports are conflicting, however, and no clear-cut delineation has been made as to which of these substances, if any, is involved in endotoxin shock.…”
mentioning
confidence: 99%